A STUDY ON RELATIONSHIP BETWEEN INTELLIGENCEN AND ACHIEVEMENT OF IXTH STANDARD STUDENTS - Ruckmani (International Journal of Research -GRANTHAALAYAH, 2016)
The present study is an attempt to study the relationship between intelligence and achievement of IX standard students. A sample of 200 students is selected from nine higher secondary schools Out of 200 students 100 are boys and 100 are girls those who are studying in secondary and higher secondary schools in IX standard in age group of 14+. Data were collected and analyzed. It is found that there is a significant difference in respect of intelligence. The study aims to investigate the relationship between achievement and intelligence parents’ level of education and occupations have no impact on the student’s achievement and intelligence of the students.